2020
DOI: 10.3390/ijms21020491
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Ca2+ Overload via Voltage-Gated Ca2+ Entry Contributes to an Anti-Melanoma Effect of Diallyl Trisulfide

Abstract: Allium vegetables such as garlic (Allium sativum L.) are rich in organosulfur compounds that prevent human chronic diseases, including cancer. Of these, diallyl trisulfide (DATS) exhibits anticancer effects against a variety of tumors, including malignant melanoma. Although previous studies have shown that DATS increases intracellular calcium (Ca2+) in different cancer cell types, the role of Ca2+ in the anticancer effect is obscure. In the present study, we investigated the Ca2+ pathways involved in the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Notably, we observed that the removal of Ca 2+ augmented the anti-melanoma effect of aspirin (Figure 4). The findings were similar to those obtained with two different apoptosis inducers, TRAIL, and the organosulfur compound diallyl trisulfide (DATS) [38,39]. Ca 2+ removal affected cell death only when cells were exposed to these pro-death stimuli, suggesting that specific Ca 2+ signals may be activated to protect cells from stress.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, we observed that the removal of Ca 2+ augmented the anti-melanoma effect of aspirin (Figure 4). The findings were similar to those obtained with two different apoptosis inducers, TRAIL, and the organosulfur compound diallyl trisulfide (DATS) [38,39]. Ca 2+ removal affected cell death only when cells were exposed to these pro-death stimuli, suggesting that specific Ca 2+ signals may be activated to protect cells from stress.…”
Section: Discussionsupporting
confidence: 81%
“…Because depolarization activates different types of VGCCs depending on its magnitude and duration, they may play a role in mediating the biological effect of aspirin. Consistent with this view, Ca 2+ channel blockers such as nifedipine and verapamil, inhibited the anti-melanoma effect (Figure 4), similar to the case for DATS [39]. Because LTCCs are the primary targets for these compounds, we further investigated their role.…”
Section: Discussionsupporting
confidence: 73%
“…DATS induced the apoptosis of human melanoma cells in a Ca 2+ ‐dependent manner. Studies investigated that DATS definitely causes Ca 2+ mit overload through non‐SOCE, thus showing the antitumor effect (Nakagawa et al, 2020). Treatment of osteosarcoma U2OS cells with different concentrations of DATS suggested that DATS induced apoptosis and arrested G0/G1 cell cycle.…”
Section: The Role Of Garlic‐derived Compound In Tumor Prevention and ...mentioning
confidence: 99%
“…Calcium channel dynamics are implicated in melanoma treatment targeting mitochondria/ER stress. Although SOCE-mediated Ca 2+ responses are critical for melanoma proliferation and apoptosis [108], drugs with anti-melanoma effects, such as diallyl trisul-fide [109], to induce mitochondrial Ca 2+ overload, ROS production, and caspase activation are mediated not by SOCEs but VDCCs. Rouaud et al reported ER stress in melanoma induced by a NADPH analog, NS1, relying on TRPM2 and Ca 2+ -activated K + channels [110].…”
Section: Targeting Calcium Mitochondria and Er Stress In Melanomamentioning
confidence: 99%